2021
DOI: 10.5194/nhess-21-629-2021
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging time series analysis of radar coherence and normalized difference vegetation index ratios to characterize pre-failure activity of the Mud Creek landslide, California

Abstract: Abstract. Assessing landslide activity at large scales has historically been a challenging problem. Here, we present a different approach on radar coherence and normalized difference vegetation index (NDVI) analyses – metrics that are typically used to map landslides post-failure – and leverage a time series analysis to characterize the pre-failure activity of the Mud Creek landslide in California. Our method computes the ratio of mean interferometric coherence or NDVI on the unstable slope relative to that of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
3
25
0
1
Order By: Relevance
“…The NDVI values are further compared with the interferometric coherence. The purpose of the comparison is to see whether some features could be obtained for early warning without complex MTI processing (Jacquemart and Tiampo 2021).…”
Section: Original Papermentioning
confidence: 99%
“…The NDVI values are further compared with the interferometric coherence. The purpose of the comparison is to see whether some features could be obtained for early warning without complex MTI processing (Jacquemart and Tiampo 2021).…”
Section: Original Papermentioning
confidence: 99%
“…Rosen et al, 1996;Tiampo et al, 2017), or landslides (e.g. Manconi et al, 2018;Handwerger et al, 2019;Dai et al, 2020b;Mondini et al, 2021;Jacquemart and Tiampo, 2021). By measuring the shift of the radar phase relative to earlier measurements of the same features, InSAR can provide measurements of ground deformation at millimeter and centimeter scales.…”
Section: Insarmentioning
confidence: 99%
“…Despite these drawbacks, many studies have shown that InSAR can be successfully applied to assess stability of slopes even in high relief terrain (e.g. Manconi et al, 2018;Handwerger et al, 2019;Bekaert et al, 2020;Jacquemart and Tiampo, 2021).…”
Section: Insarmentioning
confidence: 99%
“…NDVI có giá trị trong ngưỡng từ −1 đến +1 tương ứng với các giá trị mật độ phủ khác nhau của thực vật trên bề mặt. Chỉ số NDVI được xác định theo công thức sau [22]: Giá trị nhiệt độ bề mặt là hàm phụ thuộc vào giá trị của nhiệt độ sáng (Brightness Temperature) và phát xạ bề mặt (ε). Quá trình thu hồi các giá trị nhiệt độ bề mặt được thực hiện theo các bước sau: Bước 1.…”
Section: Thu Thập Và Chuẩn Bị Dữ Liệuunclassified